STUDY OF THE YOUTH AND JUNIOR WORLD CHAMPIONSHIPS FINALIST ADULT PERFORMANCE DEPENDING ON THE PLACES - KOVÁCS, Bálint; GYIMES, Zsolt; BENCZENLEITNER, Ottó (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2015)
The aim of the study analyses the subsequent-adulthood performance of world champion finalist male middle-distance runners from 1998 to 2012 with regards to respective competitor’s ages. The study focuses on: the finalists of the IAAF World Youth and Junior Championships (N=240), the racer’s time results at the age group world championship, and their personal bests (pb) in contrast to the location of their finals. Basic statistical analysis (mean, standard deviation - SD) and T-tests for independent samples were used to compare the average values of the group-age time results with their personal best time results. Significant progressions (p≤0,05) were found in the time results for all finishing-places in the cases of the youth and junior males, save for one exception. From the Youth World Championship finalist male middle-distance runners: only 25.9% were qualified to race at the Olympics or the World Championships. On the other hand, the junior age shows better performance in this case (50%). Investigation of the time results revealed significant progression for almost all of the prior-mentioned cases. For all examined placed runners of the Great Championships, remarkable differences were found between the youth and junior age group.